Comparison of effectiveness and awareness of recycling programme among the community between Kangar (Perlis) and Alor Setar (Kedah) - Muhamad Helmi Idris (School of Environmental Engineering, University Malaysia Perlis, 2013)
Excessive generation of solid waste resulting from the activities of the rapid development will be an important issue that cannot be avoided in time to come in countries that are being built.